(untitled)
The paper proves the nonexistence of the solution for the following Cauchy problem align*casesu_t =div(| abla u^m |^p-2 abla u^m )-λ u^q,&(x,t)S_T =R ^N × (0,T), u(x, 0)=δ (x), &xR ^N,casesalign* under some conditions on m, p, q, λ, where δ is Dirac function. , number=4, journal=Journal of Partial Differential Equations, year=2021, month=Aug., pages=369–378